A novel chaotic interleaving algorithm for mobile wireless channels - Xianping WANG; Hui CAO (Dianxin kexue)
Interleaving technique is an efficient technique to resist serious burst errors over mobile wireless fading channels.To resist 2 dimensionality burst errors effectively,a novel chaotic interleaving algorithm based on Baker map was proposed.In the proposed scheme,the binary source sequence was converted to the data matrix,and then the data matrix was dispersed randomly by using the chaotic Baker map approach,in order to realize the function of transforming 2 dimensionality long bust error into the short 1 dimensionality short bust error after de-interleaving.In additional,the proposed algorithm was combined with the convolution code based on Viterbi decoding,and was applied into the scenario of convolutional codes (2,1,3) and the scenario of (2,1,7) separately for a performance comparison.The simulation results show that the performance of the proposed algorithm outperforms better than the traditional algorithms under image transmission over mobile wireless channel.Moreover,the anti-fading capability of the proposed algorithm grows as the packet length increases,while reducing the complexity significantly.Finally,the chaotic interleaver can also enhance every transmitted packet's security with different secret keys.